2014
DOI: 10.1177/2047487314528872
|View full text |Cite
|
Sign up to set email alerts
|

Confusion in reporting pulmonary diffusing capacity for nitric oxide and the alveolar-capillary membrane conductance for nitric oxide

Abstract: We read with interest the paper by Magini and colleagues on the measurement of pulmonary diffusing capacity for nitric oxide in patients with heart failure (ejection fraction<40%).1 In their study they report pulmonary diffusing capacity and the individual components of pulmonary diffusing capacity in 50 patients with heart failure (65 years of age), and 50 control subjects (61 years of age). We feel that there are two problems with this paper that warrant discussion. First, the mean values for pulmonary diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In liver cirrhosis with hepatopulmonary syndrome (HPS) [74], there was a greater reduction in VC and DMCO (and a lower arterial oxygen pressure) versus non-HPS patients, but both groups demonstrated a similar rise in DLNO/DLCO and DMCO/VC ratios compared to controls, consistent with microvascular disease. In heart failure, DLNO/DLCO and DMCO/VC ratios were reported to be increased [75], contrary to predictions, but there were methodological issues in the calculations of DMCO/VC [76]. As such, more studies are needed examining microvascular disease and its effects on diffusing capacity.…”
Section: Microvascular Diseasementioning
confidence: 87%
“…In liver cirrhosis with hepatopulmonary syndrome (HPS) [74], there was a greater reduction in VC and DMCO (and a lower arterial oxygen pressure) versus non-HPS patients, but both groups demonstrated a similar rise in DLNO/DLCO and DMCO/VC ratios compared to controls, consistent with microvascular disease. In heart failure, DLNO/DLCO and DMCO/VC ratios were reported to be increased [75], contrary to predictions, but there were methodological issues in the calculations of DMCO/VC [76]. As such, more studies are needed examining microvascular disease and its effects on diffusing capacity.…”
Section: Microvascular Diseasementioning
confidence: 87%
“…In recent years, most scientists have agreed that the most correct values for θCO are those presented by FORSTER [11] in 1987, and thereby not the 1957 values presented by ROUGHTON and FORSTER [2]. Forster himself argued that these new values were more correct, particularly since they were measured at a physiological pH of 7.4 and not pH 8.0 like the 1957 values [9,12,14]. In 2016, GUÉNARD et al [41] tested several of the available 1/θCO versus PcapO 2 equations by exposing 10 normal subjects to two different inspiratory oxygen concentrations while measuring DLNO and DLCO.…”
Section: θCo θNo and αmentioning
confidence: 99%
“…In the work of GUENARD et al [3], θNO was assumed to be infinitely great, since it had been shown earlier that the reaction rate of NO with free haemoglobin (Hb) was 250-1400 times faster than for CO [2,3,5,6]. However, in recent years the correctness of this assumption has been thoroughly debated and recent evidence points towards θNO being finite, with a value of 4.5 mLNO•mLblood −1 •min −1 •mmHg −1 [7][8][9][10]. This value is used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Lung mechanics and pulmonary diffusing capacity are compromised in those with heart failure (HF) (Agostoni et al, 2006;Magini et al, 2015;Zavorsky and Borland, 2015). The former is characterized by lung restriction, while pulmonary diffusion capacity for carbon monoxide (DLCO) is impaired due to a reduction in both alveolar-capillary membrane diffusing capacity for CO (DMCO) (Puri et al, 1995) and pulmonary capillary volume (Vcap) (Magini et al, 2015;Zavorsky and Borland, 2015). Historically, DM is calculated from DLCO through the Roughton and Forster multi-step technique where 1/DLCO= 1/DM + 1/θCO•VCap), where θco is the specific conductance in the blood for CO (Roughton and Forster, 1957).…”
Section: Introductionmentioning
confidence: 99%